Concluding observations: citizenship in cities, states and empires. Issue 3 (3rd April 2019) - Stuurman, Siep
ABSTRACT: Looking back on the contributions to this issue, this essay situates citizenship in the frame of state formation. It places the varieties of citizenship on a continuum, from punctual citizenship acts to the normative and highly demanding Aristotelian concept of citizenship. All premodern states, with the exception of China, were infra-structurally weak, leaving room for self-rule and citizenship acts in local, often urban, arenas. However, citizenship was also found in larger – frequently federal – states. In many states in pre-colonial Asia, people defended their entitlements, negotiated with the ruling elites and, though less often, participated in government. This resulted in 'quasi-rights', not guaranteed by written charters, and yet efficacious in limiting the power of the governing class. Apart from political citizenship, the essay discusses forms of social citizenship, in particular in the sphere of gender regimes. The conclusion situates eight degrees and varieties of citizenship and citizenship acts in the context of state-formation in world history.